THU0677 Outcome measurement instruments for safety in rheumatology: a scoping review of available instruments to inform the omeract safety working group. (15th June 2017) - Klokker, L; Woodworth, T; Furst, DE; Tugwell, P; Devoe, D; Williamson, P; Terwee, CB; Suarez-Almazor, ME; Strand, V; Leong, AL; Goel, N; Boers, M; et al.
Abstract : Background: International scientific networks have raised concerns about inadequate reporting of safety outcomes in randomised trials and systematic reviews. Outcome Measures in Rheumatology (OMERACT) has previously developed an adaptation of the US National Cancer Institute (US NCI) Common Terminology Criteria for Adverse Events (CTCAE), the RCTC (Rheumatology Common Toxicity Criteria) to collect adverse events in rheumatology clinical trials. To respond to the need to also report safety outcomes from the patient perspective, the Safety Working Group is developing a core outcome set, followed by a core outcome measurement set. A scoping review of available instruments for measuring safety outcomes is needed to inform this work. Objectives: To identify candidate measurement instruments for safety outcomes in rheumatology clinical trials. Methods: A systematic search was performed in the MEDLINE database (via PubMed) in January 2017 using MeSH terms covering synonyms for adverse events, rheumatology and measurement instruments and the Boolean operator AND to combine them. Full-text articles about the development or evaluation of instruments for measuring safety in rheumatology were eligible. One reviewer (LK) screened for eligibility based on title and abstracts. Two reviewers (LK and RC) screened the full text articles. Results: Of 434 unique references identified, 19 were read in full-text, and 8 were included (see figure). The instruments identified were: Glucocorticoid Toxicity Index (GTI), Patient Reported Experiences and Outcomes of Safety in Primary Care (PREOS-PC), Safety of Estrogens in Lupus Erythematosus National Assessment (SELENA)-SLEDAI flare index (cSFI), the BioSecure questionnaire, Rheumatology Common Toxicity Criteria (RCTC), OMERACT 3x3, and the Stanford Toxicity Index (STI). These instruments were specific for substance (GTI, BioSecure questionnaire), setting (PREOS-PC), condition (cSFI), or not fully validated (RCTC, OMERACT 3x3, STI). Conclusions: The instruments identified are either too specific, or require further development/evaluation, for the purpose of standardizing measurement of safety in rheumatology clinical trials. Thus, we will proceed to gain consensus on the domains that must be measured to develop a core outcome set. Disclosure of Interest: None declared